Study on the Influence of Live Broadcast Characteristics on Customer Value Co-Creation Behaviors: The Mediating Role of Interactive Attitudes - Zhang, Lining (Transactions on Economics, Business and Management Research, 2024)
Value co-creation behaviors (VCCB) are essential to promote resource integration. However, few studies have explored VCCB in the field of live e-commerce broadcasting. Therefore, this paper distinguishes the live broadcast features from the e-commerce anchor characteristics and agricultural product characteristics to explore their influence mechanisms on customer participation and citizenship behaviors, respectively. Through the questionnaire survey, 353 original data were collected for empirical testing. The results showed that the characteristics of live broadcasts (e-commerce anchor characteristics and agricultural product characteristics) significantly affected the VCCB. Interactive attitudes are an intermediary between live broadcast characteristics and VCCB.